2002
DOI: 10.1300/j049v10n01_02
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Internet Retailing

Abstract: Dissimilar to non-electronic retailing, Internet retailing does not have well-developed typologies that identify underlying factors for differentiating on-line participants. Development of a typology for Internet retailers allows researchers to more fully understand channel dimensions and provide researchers with a tool for tracking and predicting the structure of Internet retailing. This study fulfills this need by combining both existing retailing attributes and unique features of e-retailing to appraise a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As a tool for segmenting markets and profiling consumers, cluster analysis has been extensively used by previous studies (Christodoulides et al, 2013;Maier and Saunder, 1990;Mottner et al, 2002;Prashar et al, 2016). As suggested by Hair et al (2006), multistep cluster analysis was used to classify the respondents on the bases of their choice criteria for defining online shopping experience.…”
Section: Cluster Analysismentioning
confidence: 99%
“…As a tool for segmenting markets and profiling consumers, cluster analysis has been extensively used by previous studies (Christodoulides et al, 2013;Maier and Saunder, 1990;Mottner et al, 2002;Prashar et al, 2016). As suggested by Hair et al (2006), multistep cluster analysis was used to classify the respondents on the bases of their choice criteria for defining online shopping experience.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Therefore, logistics expenses have replaced store-related costs as the main retail expense (Soasta, 2012). In this regard, in the 21st century logistics has been recognized as a core competence contributing to eretailers' competitiveness, in the new robust marketplace (Maltz et al, 2004;Mottner et al, 2002). Therefore, the e-retailers need advanced retail information systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study from the manufacturing sector identified types of adopters based on patterns of adoption in the supply chain (Craighead and LaForge, 2003), but did not examine beliefs. A quantitative analysis of retail web sites by Mottner et al (2002) created a typology of e-tail web sites according to the functions they performed (intermediary, product focused e-tailer, and micro-segment focused e-tailer) without examining the retail owners' beliefs. However, the literature does provide information about beliefs likely important to small, rural retailers deciding to use the internet.…”
Section: Literature Reviewmentioning
confidence: 99%